A micromechanical model for the swelling effect on visco-super-elastic and damage self-healing behaviors of hydrogels reinforced by nanoparticles. (January 2023) - Saadedine, Mahrez; Zaïri, Fahmi; Ouali, Nourdine; Tamoud, Abderrahman; Ding, Ning; Mesbah, Amar
Abstract: In the present article, a micromechanical model is developed for the visco-super-elastic behavior of swollen hydrogel-based nanocomposites. The model formulated in a finite strain context introduces explicitly the hydrogel network features in terms of swelling and dynamic breaking-recombination. The effective interactions between the nanoparticles and the swollen hydrogel network are considered using a micro-macro scale transition within the Eshelby inclusion theory. The model is compared to experimental observations of a high-swelling capacity hydrogel-based nanocomposite reinforced with different concentrations of nanoparticles. The model is firstly identified using experimental data at an initial swelling state in terms of stress-strain response, energy dissipation and ultimate properties. The predictive capability of the model is then verified on a wide range of swelling ratios for a given nanofiller concentration. The efficiency of the model is further critically discussed by comparisons with history-dependent data under stretching-retraction and self-healing. The effects of nanoparticles and swelling on the self-healing behavior are shown thanks to the model. Highlights: We assess the visco-super-elastic mechanics of swollen hydrogel-based nanocomposites. We propose a model connecting overall mechanics to nanostructure and hydrogel network features. We describe the swelling effect on the mechanisms of nanoparticles reinforcement and failure. We predict the swelling effect on the room temperature self-healing facility in connection to nanostructure.